A protocol and calibration method for accurate multi-camera field videography - Theriault, D. H.; Fuller, N. W.; Jackson, B. E.; Bluhm, E.; Evangelista, D.; Wu, Z.; Betke, M.; Hedrick, T. L. (The Journal of Experimental Biology, 2014)
Stereo videography is a powerful technique for quantifying the kinematics and behavior of animals, but it can be challenging to use in an outdoor field setting. We here present a workflow and associated software for performing calibration of cameras placed in a field setting and estimating the accuracy of the resulting stereoscopic reconstructions. We demonstrate the workflow through example stereoscopic reconstructions of bat and bird flight. We provide software tools for planning experiments and processing the resulting calibrations that other researchers may use to calibrate their own cameras. Our field protocol can be deployed in a single afternoon, requiring only short video clips of light, portable calibration objects.